Pengaruh Model Pembelajaran Cettar Membahana dalam Menumbuhkembangkan Kemampuan Literasi, Numerasi dan Karakter Malaqbiq Siswa SMP - Ahmad Syah; Fatima Fatima; Muhammad Assaibin (SUPERMAT (JURNAL PENDIDIKAN MATEMATIKA), 2023)
This research is motivated by literacy and numeracy skills as one of the implementations of independent learning proclaimed by the Ministry of Education and Culture which is growing, so that teachers and various parties are always trying and innovating to continue to develop students' literacy and numeracy abilities. This study aims to determine how the influence of the Cettar-Membahana learning model can develop students' literacy and numeracy skills and Malaqbiq character. The research to be used is quasi-experimental research which aims to determine the effect of applying the Cettar Familiar model in developing students' numeracy literacy skills and Malaqbiq character. The research design used was a pre-test/post-test control group where Class VII B served as the experimental class and VII A as the control class, each consisting of 20 students. This research was conducted at SMP Negeri 7 Polewali, Polewali Mandar Regency. This study's results indicate that using the Cettar Memorizing learning model can develop students' literacy, numeracy, and malaqbiq character. This can be seen from the results of the analysis of student activities which show they are in the very active category (92.3%), the implementation of learning is in the well-implemented category (100%), and the average results of literacy and numeracy abilities are in the very high category (81). Therefore, this study can be concluded that the Cettar Memorization learning model has an effect on developing students' numeracy literacy skills and malaqbiq characters.